Peningkatan Volume Penjualan Miso Buk Tura Melalui Analisis Strategi Bauran Pemasaran - Nova Sari Manullang; Genta Lutfi Djaingsastro; Tohap Marhasak Sripandi Hutasoit (Economic Development Progress, 2025)
This study was conducted with the main objective of identifying and describing the implementation of marketing strategies applied by Miso Buk Tura to encourage an increase in their sales volume. The chosen research methodology is a descriptive qualitative approach, where data collection was carried out through a combination of in-depth interviews and observations, utilizing primary and secondary data as sources of information, while the applied data analysis was based on description, focusing on the 4P Marketing Mix framework (Product, Price, Place, and Promotion). The results of the analysis indicate that Miso Buk Tura employs a number of tactics to boost sales, including: the Product strategy which focuses on maintaining the consistent quality and distinctive flavor of their Miso over time, the Price strategy by offering competitive and affordable pricing, the Place strategy by choosing a strategic business location to ensure optimal accessibility, and the Promotion strategy which involves utilizing social media platforms. The integrated implementation of these marketing mix strategies has proven to contribute significantly to Miso Buk Tura's sales volume, characterized by a continuous upward trend in sales since its establishment until the present day.